Dynamic Income, Progressive Taxes, and the Timing of Charitable Contributions - Randolph, William C. (Journal of Political Economy, 1995)
Using an econometric model of charitable giving and a ten-year panel of tax return data, the author finds that previous studies have underestimated the effects of permanent income and overestimated those of permanent changes in tax prices. The significant statutory tax changes that occurred during the 1980s, especially in 1986, serve to identify the key model parameters. The author's results imply that people smooth their giving when transitory income changes but also time their giving to exploit transitory changes in tax prices. The results also raise questions about how effectively the tax incentives permanently influence the level of charitable giving by individuals. Copyright 1995 by University of Chicago Press.